Experimental results on electrorheology of liquid crystalline polymer solutions - Neves, S. (2008)
The electrorheological (ER) effect is known as the enhancement of the apparent viscosity upon apphcation of an external electric field. Suspensions of polarizable particles in non-conducting solvents are the most studied electrorheological fluids, however, liquid crystalline materials may also present ER effect as long as their dielectric anisotropy is positive. In the liquid crystalline state of a positive dielectric anisotropy, the application of the electric field makes the director align perpendicular to the fiow direction, thus increasing the apparent viscosity. In this work results of two liquid crystalline polymer solutions, acetoxypropylcellulose (APC) in dimethylacetamide (DMAc) and poly-y-benzyl-L-glutamate (PBLG) in 1,4-dioxane, presenting opposite behavior upon application of the electric field, will be presented. APC/DMAc (negative dielectric anisotropy) presents a decrease of the apparent viscosity upon application of the electric field, as expected, while PBLG/l,4-dioxane (positive dielectric anisotropy) presents the opposite behavior. For this last solution we will present the shear fiow curves for different electric fields in function of polymer molecular weight and solution concentration.